Application of Cord Blood–Derived Exosomes in Tumor Prevention and Treatment - Chen Huang; Yongsheng Li; Baozhong Zhang; Yukuan Tang; Yuyang Huang; Wei Wei (Clinical Medicine Insights: Oncology)
The eradication of tumors remains a critical and challenging issue in medical research. Exosomes (EXOs) derived from various sources have garnered increasing attention in the field of tumor therapy. Among these, cord blood (CB)-derived EXOs may offer unique advantages in combating tumors due to the distinctive properties of CB. This narrative review examines the current application status of CB-derived EXOs in tumor prevention and treatment: in the context of tumor treatment, it focuses on their direct therapeutic application and their use as drug carriers; regarding tumor prevention, it explores their application in cancer vaccines. In addition, it also reviews the specific components of CB from which these EXOs are derived, their particle sizes, characteristic proteins, and the types of tumors to which they have been primarily applied for prevention and treatment. In conclusion, we believe that CB-derived EXOs hold substantial potential for effective tumor prevention and treatment and are likely to emerge as a prominent area of research in the future.